Effects of different doses of bokashi on the production of Lactuca Sativa L. (Research, Society and Development, 2024)
Lettuce (Lactuca sativa L.) is present in the diet of most Brazilians and in the harvest of a large number of agricultural producers, due to its expansiveness and ease of cultivation when compared to other vegetables. In addition to its energetic and nutritional value, it provides accessibility due to its cost and short development cycle, generating a strong economic and social impact. The quality of the soil used symbolizes one of the main factors in production, due to the dependence on this efficiency for the success of the final product, as well as the purity of the seeds used and their germination potential. Bokashi organic fertilizer assumes an essential function, the use of beneficial microorganisms being necessary to keep the soil in balance and generate productivity in seed preparation, in addition to being ecologically profitable because it does not have aggressive properties for the producer; environment and the consumer. The objective of the present work was to analyze the IVE and IE indices from the effects of using the organic compound bokashi at different concentrations on the production of Lactuca sativa L. The experiment was carried out in a greenhouse located at the Universidade Estadual de Alagoas - UNEAL Campus I. A completely randomized experimental design (DIC) was used, with five treatments of different bokashi doses (T1- control; T2- 5%; T3- 10%; T4- 15%; T5- 100%). The data were submitted to analysis of variance, with the aid of the SISVAR statistical program, concluding that the use of biofertilizer had a positive effect on the final indices, with relevance to the concentration of 10% and 15%.